2020
DOI: 10.1172/jci134132
|View full text |Cite
|
Sign up to set email alerts
|

Orally bioavailable CDK9/2 inhibitor shows mechanism-based therapeutic potential in MYCN-driven neuroblastoma

Abstract: The undruggable nature of oncogenic Myc transcription factors poses a therapeutic challenge in neuroblastoma, a pediatric cancer in which MYCN amplification is strongly associated with unfavorable outcome. Here, we show that CYC065 (fadraciclib), a clinical inhibitor of CDK9 and CDK2, selectively targeted MYCN -amplified neuroblastoma via multiple mechanisms. CDK9 — a component of the transcription elongation complex P-TEFb — bound to the MYCN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 58 publications
2
42
0
Order By: Relevance
“…A covalent inhibitor of CDK7, THZ1, selectively targets MYCN -amplified neuroblastoma cells, leading to global suppression of MYCN -dependent transcriptional amplification and sustained growth inhibition of tumors in a mouse model of neuroblastoma ( 85 ). CYC065 (fadraciclib), a clinical inhibitor of CDK9 and CDK2 (a major regulator of apoptotic cell death), selectively targets MYCN -amplified neuroblastoma through a loss of MYCN transcription and growth arrest, followed by sensitizing cells for apoptosis as a result of CDK2 inhibition ( 86 ). Furthermore, the combined use of CYC065 with temozolomide (a reference therapy for relapsed neuroblastoma), leads to long-term repression of neuroblastoma growth in vivo ( 86 ).…”
Section: Regulation Of Mycn Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A covalent inhibitor of CDK7, THZ1, selectively targets MYCN -amplified neuroblastoma cells, leading to global suppression of MYCN -dependent transcriptional amplification and sustained growth inhibition of tumors in a mouse model of neuroblastoma ( 85 ). CYC065 (fadraciclib), a clinical inhibitor of CDK9 and CDK2 (a major regulator of apoptotic cell death), selectively targets MYCN -amplified neuroblastoma through a loss of MYCN transcription and growth arrest, followed by sensitizing cells for apoptosis as a result of CDK2 inhibition ( 86 ). Furthermore, the combined use of CYC065 with temozolomide (a reference therapy for relapsed neuroblastoma), leads to long-term repression of neuroblastoma growth in vivo ( 86 ).…”
Section: Regulation Of Mycn Transcriptionmentioning
confidence: 99%
“…CYC065 (fadraciclib), a clinical inhibitor of CDK9 and CDK2 (a major regulator of apoptotic cell death), selectively targets MYCN -amplified neuroblastoma through a loss of MYCN transcription and growth arrest, followed by sensitizing cells for apoptosis as a result of CDK2 inhibition ( 86 ). Furthermore, the combined use of CYC065 with temozolomide (a reference therapy for relapsed neuroblastoma), leads to long-term repression of neuroblastoma growth in vivo ( 86 ).…”
Section: Regulation Of Mycn Transcriptionmentioning
confidence: 99%
“…Cyclin dependent kinases such as CDK7 and CDK9 play a key role in regulating transcriptional activity of MYCN (141)(142)(143).…”
Section: Targeting Mycn Transcriptional Activitymentioning
confidence: 99%
“…Cyclin dependent kinases such as CDK7 and CDK9 play a key role in regulating transcriptional activity of MYCN ( 141 143 ). We have identified strong enrichment for CDK9 at both the MYCN promoter and the distal super enhancer and shown that pharmacologic blockade of CDK9 using Fadraciclib targeted MYCN-dependent transcriptional landscape ( 143 ).…”
Section: Emerging Therapeutic Opportunitiesmentioning
confidence: 99%
“…Indeed, THZ1, a covalent inhibitor of CDK7, was found to selectively target MYCN -amplified NB cells, leading to global repression of MYCN -dependent transcriptional amplification and reductions in expression of SE-associated oncogenic drivers including MYCN itself and suppression of NB tumor xenograft growth ( 87 ). CYC065, an inhibitor of CDK9 and CDK2, was found to selectively target MYCN-amplified NB cells by leading to a selective loss of nascent MYCN transcription ( 105 ). These studies indicate that the inhibition of CDK7 or CDK9 can be exploited to disrupt aberrant MYCN -driven transcription and to repress MYCN gene transcription as a therapeutic for MYCN -driven cancers ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%